Claiming the land or protecting the goods? The Duchcov hoard in Bohemia as a proxy for 'Celtic migrations' in Europe in the 4th century BCE. (March 2021) - Danielisová, Alžběta; Pajdla, Petr; Bursák, Daniel; Strnad, Ladislav; Trubač, Jakub; Kmošek, Jiří
Abstract: The paper presents a geochemical analysis of a remarkable assemblage from the early La Tène period (4th century BCE): the Duchcov hoard found in the late 19th century in north-western Bohemia. More than a thousand pieces of bronze jewellery (mostly brooches and bracelets) in a bronze cauldron were deposited in a natural spring. This possibly ritual offering of unknown purpose might have involved a large community whose origin and structure could be discussed using archaeometric data from the hoard. The typologically and chronologically highly homogeneous assemblage with stylistic parallels across western and central Europe offers a unique opportunity to study Iron Age bronze metalworking, for which scientific data in Europe are still sparse. The assemblage was studied using a range of methods to derive information on the composition of the alloys and to determine their provenance using trace element patterns and lead isotope analysis. The results show that this seemingly homogeneous assemblage contains several chemically distinctive groups that are compatible with the spread of the so-called Duchcov-Münsingen horizon in the 4th century BCE. Mobility patterns or economic networks that may have resulted in such diverse geochemical data are discussed. The paper also discusses the multi-statistical approach to evaluating data in order to determine provenance. The findings and their narrative are discussed in the historical framework of the 'Celtic migrations' in Europe in the 4th century BCE. Highlights: First publication of the geochemical analysis of early La Tène objects in Europe. Lead isotopes revealed a remarkably wide geographical spread for the samples. Object origins identified across western and central Europe. Robust statistical methods were used to discuss provenance. The provenance of metals is linked either to people's mobility patterns or possible exchange networks.